2017
DOI: 10.1073/pnas.1701030114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the nucleus–vacuole junction based on the Vac8p–Nvj1p crystal structure

Abstract: Formation of the nucleus-vacuole junction (NVJ) is mediated by direct interaction between the vacuolar protein Vac8p and the outer nuclear endoplasmic reticulum membrane protein Nvj1p. Herein we report the crystal structure of Vac8p bound to Nvj1p at 2.4-Å resolution. Vac8p comprises a flexibly connected N-terminal H1 helix followed by 12 armadillo repeats (ARMs) that form a right-handed superhelical structure. The extended 80-Å-long loop of Nvj1p specifically binds the highly conserved inner groove formed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 44 publications
12
64
0
Order By: Relevance
“…The loop (residues 35-40) bridging the H1 helix and the first ARM (ARM1) is disordered in the structure ( Figure 1D). The overall conformation of the 12 concerted ARMs of tVac8 observed in the crystal structure of the tVac8-tAtg13 complex was essentially identical to that observed in the tVac8-tNvj1 complex [24], with a root-mean-square deviation (RMSD) value of 0.88 Å for all Cα atoms. The 70-Å extended loop of Atg13 binds across the inner groove formed by the central ARMs of Vac8 ( Figure 1C).…”
Section: Structure Of Tvac8 In Complex With Tatg13mentioning
confidence: 56%
See 2 more Smart Citations
“…The loop (residues 35-40) bridging the H1 helix and the first ARM (ARM1) is disordered in the structure ( Figure 1D). The overall conformation of the 12 concerted ARMs of tVac8 observed in the crystal structure of the tVac8-tAtg13 complex was essentially identical to that observed in the tVac8-tNvj1 complex [24], with a root-mean-square deviation (RMSD) value of 0.88 Å for all Cα atoms. The 70-Å extended loop of Atg13 binds across the inner groove formed by the central ARMs of Vac8 ( Figure 1C).…”
Section: Structure Of Tvac8 In Complex With Tatg13mentioning
confidence: 56%
“…Based on these data, we made a truncated Atg13 construct (residues 567-695; designated as tAtg13) for structural analysis of the tVac8-tAtg13 complex. tVac8 (residues 10-515) was used in our previous study ( Figure 1A) [24]. Analytical ultracentrifugation (AUC) experiment revealed that the tVac8-tAtg13 complex formed a heterodimer in solution ( Figure 1B).…”
Section: Structure Of Tvac8 In Complex With Tatg13mentioning
confidence: 92%
See 1 more Smart Citation
“…Although NVJs have not been specifically shown to mediate lipid transfer between the vacuole and NE, interorganelle contact sites often serve as sites of lipid exchange (Kornmann et al, 2009;Elbaz-Alon et al, 2014) due to their close apposition and enrichment of lipid-exchanging factors. The ergosterol-and PI(4)P-binding protein Osh1 (Manik et al, 2017), which is found at NVJs and interacts with Nvj1 (Jeong et al, 2017;Kvam and Goldfarb, 2004;Levine and Munro, 2001), belongs to the oxysterol-binding homology protein family that can aid in lipid transfer between membranes (de Saint-Jean et al, 2011). Additionally, LDs are thought to promote lipid transfer between organelles, potentially through "lipid bridges" (Schuldiner and Bohnert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although morphologically distinct, vacuoles are functionally similar to metazoan lysosomes, serving as acidic organelles involved in protein degradation and nutrient storage. Several outer NE membrane proteins including Nvj1 (Pan et al, 2000) and Mdm1 (Henne et al, 2015) are present at NVJs and tether the NE to the vacuole through specific interactions with corresponding vacuolar proteins like Vac8 (Pan et al, 2000;Jeong et al, 2017) or phospholipid species such as phosphatidylinositol 3-phosphate (Henne et al, 2015). NVJs expand when cells are grown using carbon sources other than glucose (Hariri et al, 2018;Bean et al, 2018) or to promote piecemeal autophagy of the nucleus (PMN) in response to nutrient starvation , which involves autophagy-dependent degradation of specific nuclear proteins in the vacuole (Krick et al, 2008).…”
Section: Introductionmentioning
confidence: 99%